Pengaruh Endorphin Massage Terhadap Intensitas Nyeri Pada Ibu Bersalin Kala I di BPM Rini Susianti., Amd.Keb - Kholifatul Marhamah, Siti; Rini Susianti; Ria Elita; Revi Anggraini; Vitra Vica; Aina Aina (Pusat Riset dan Inovasi Nasional, 2022)
The labor process is related to pregnant women's pain during childbirth, especially during the active phase of vaginal delivery in the first stage. It is necessary to do a way to reduce or even eliminate the pain felt by mothers giving birth. One method that can be applied is endorphin massage, a light category touch technique in pain management and relaxation. The purpose of this study was to determine the effect of endorphin massage on the intensity of pain in the first stage. The research design applied was a case study method with pretest and posttest designs. The sample in the study is Mrs. A, 22 years, G2P1A0, UK, 38 weeks five days. The research activity was carried out on May 16, 2022. The research instrument used a numerical rating scale (NRS) with a scale of 1-10; a score of 0 was painless, a score of 1-3 was mild pain, a score of 4-6 was moderate pain, a score of 7-10 was severe pain. The research method was carried out by providing endorphin massage therapy with the mother lying on her side, a pillow on the back of the back, and between the legs where it was for support. Then apply moderate pressure for 10 minutes. Massage from the head and neck than on the back, waist, and legs. The results obtained a scale value of number 7 before treatment and number 4 after an endorphin massage treatment, which means that there is an effect of giving endorphin massage to decrease the intensity of pain that occurs in first-stage mothers.